Measuring the Equilibrium Effects of Unemployment Benefits Dispersion - Aico van Vuuren; Gerard J. van den Berg; Geert Ridder (Tinbergen Institute, 1999)
We analyze the impact of unemployment benefits and minimum wagesusing an equilibrium search model which allows for dispersion ofbenefits and productivity levels, job-to-job transitions, andstructural and frictional unemployment. The estimation method usesreadily available aggregate data on marginal distributions ofunemployment durations as well as wages and benefit levels.Different causes of structural and frictional unemployment areinvestigated. We investigate the efficiency of the imposition of asingle benefit level for all household types and the introductionof an Earned Income Tax Credit.
Keywords: 330; Arbeitslosenversicherung; Mindestlohn; Grundeinkommen; Theorie; Großbritannien